An ancient evolutionary origin of the Rag1/2 gene locus - Fugmann, Sebastian D. (National Academy of Sciences, 2006)
The diversity of antigen receptors in the adaptive immune system of jawed vertebrates is generated by a unique process of somatic gene rearrangement known as V(D)J recombination. The Rag1 and Rag2 proteins are the key mediators of this process. They are encoded by a compact gene cluster that has exclusively been identified in animal species displaying V(D)J-mediated immunity, and no homologous gene pair has been identified in other organisms. This distinctly restricted phylogenetic distribution has led to the hypothesis that one or both of the Rag genes were coopted after horizontal gene transfer and assembled into a Rag1/2 gene cluster in a common jawed vertebrate ancestor. Here, we identify and characterize a closely linked pair of genes, SpRag1L and SpRag2L, from an invertebrate, the purple sea urchin (Strongylocentrotus purpuratus) with similarity in both sequence and genomic organization to the vertebrate Rag1 and Rag2 genes. They are coexpressed during development and in adult tissues, and recombinant versions of the proteins form a stable complex with each other as well as with Rag1 and Rag2 proteins from several vertebrate species. We thus conclude that SpRag1L and SpRag2L represent homologs of vertebrate Rag1 and Rag2. In combination with the apparent absence of V(D)J recombination in echinoderms, this finding strongly suggests that linked Rag1- and Rag2-like genes were already present and functioning in a different capacity in the common ancestor of living deuterostomes, and that their specific role in the adaptive immune system was acquired much later in an early jawed vertebrate.